Isolasi dan Identifikasi Bakteri Selulolitik pada Sampah Organik di TPA Suwung Denpasar - FADEL ALKAHFI; WAYAN ADIARTAYASA; I GEDE PUTU WIRAWAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Isolation and Identification of Cellulolytic Bacteria in Organic Waste at TPA Suwung Denpasar Organic waste contains a lot of lignocellulosic material which can be degraded by cellulases. The degradation of cellulose requires three types of enzymes produced by microorganisms. Cellulolytic bacteria are one of the microorganisms involved in the decomposition process and produce cellulase enzymes which can degrade organic matter. This study aims to isolate and test the ability of cellulolytic bacteria in the organic waste of TPA Suwung Denpasar by isolating morphological identification, and quantitative cellulase test. The results of this study found twenty-seven (27) bacterial isolates that were able to grow on CMC media and were classified based on colony morphology and obtained 3 different isolate groups. The isolates that had been grouped were coded A, B, and C. The colony of the isolated isolates appeared to be round and wrinkled. Some surfaces are convex, raised, and hilly and are clear, yellows in color, and white. Isolates A and C were gram positive, while isolate B was gram negative. Based on the calculation results of the Cellulolytic Index value, it was found that isolate B had the highest IS and was in the high category.